Unravelling the synthetic and therapeutic aspects of five, six and fused heterocycles using Vilsmeier-Haack reagent - Chahal, Mamta; Dhillon, Sudeep; Rani, Priyanka; Kumari, Ginna; Aneja, Deepak Kumar; Kinger, Mayank (RSC advances, 2023)
The aim of this review is to encapsulate the synthetic protocols and medicinal aspects of a wide range of heterocyclic compounds using the Vilsmeier-Haack (V. H.) reagent. These derivatives act as excellent precursors having different aryl ring functionalities and could be used for the synthesis of a variety of heterocyclic scaffolds. The V. H. reagent, a versatile reagent in organic chemistry, is used to formylate various heterocyclic compounds of medicinal interest. Due to the different chemical interactions, efficacy, and potency of V. H. reagents, plenty of heterocyclic compounds can be synthesized which serve as a constituent in various novel medications and acts as a bridge between biology and chemistry. These carboxylate moieties can effectively cooperate as precursors for several multi-component reactions (MCR) including Strecker synthesis, Bucherer-Berg reaction and post-MCR cyclization, modified variants with various pharmaceutical applications such as anti-tumor, anti-convulsant, anti-chitosomal and so on. The aim of this review is to encapsulate the synthetic protocols and medicinal aspects of a wide range of heterocyclic compounds using the Vilsmeier-Haack (V. H.) reagent.